Beautiful bodies in virtual environments: study by visual sociology - doi: 10.4025/reveducfis.v23i3.16987 - Marcelo Callegari Zanetti; Altair Moioli; Mauro Klebis Schiavon; Flávio Rebustini; Afonso Antonio Machado (Journal of Physical Education (Maringá), 2012)
The beautiful body was always present in the imagination and desire of people who increasingly resort to resources in order to achieve such beauty. Nowadays this beauty is also sought in the construction of avatars and virtual environments seems to contaminate. Therefore, we conducted a study aiming to investigate these beautiful environments, represented by avatars in the game Second Life. As a methodological proposal investigated 28 people in eight different environments. In analyzing the data we chose to use visual sociology. The main results we find the construction of avatars with physical attributes desired by our current society, in which women seek to explore the sensuality and the physical force men. These results led us to conclude that physical standards can be worshiped widely found in these environments.